From Ethics to Expertise in Socially Responsible Investment - Secreteanu, Catalina (2009)
This dissertation aims to analyze how an organization engaged in the Socially Responsible Investment Industry created and developped its ethical identity. I have adopted an ethnographic approach in order to collect and understand the organizational narratives and to explore the relationship between the ethical identity of the organization and the concepts of identity, culture and image. The project exemplifies how people in the organization made sense of the company’s identity and culture. I illustrate that the organization has multiple and competing narratives, many people in the organization experiencing a fragmented organizational culture, and a lack of meaning in their everyday job. The re-branding of the company from the Ethical Investment Services to Experts in Responsible Investment Solutions possibly triggers a form of organizational change, re-positioning the organization in the SRI industry. The dissertations argues that organizations engaged in developing business environments should pursuit internal organizational change, and ensure congruence between organizational identiy, culture and image. The project concludes by stating that the ethical legacy of the company should be maintained and integrated within the changing organizational structures.